10.1016/S0271-7964(08)70554-8 (CrossRef Listing of Deleted DOIs, 2000)
Background Preterm neonates are at high risk of morbidity and mortality due to physiological immaturity and susceptibility to complications. The prognostic nutritional index (PNI), calculated from serum albumin and lymphocyte counts, is an inflammation-based biomarker widely used to predict prognosis in adult diseases. However, its role in neonatology remains unclear. Objective To evaluate the association between PNI and early mortality in preterm infants. Methods Preterm infants born at < 32 weeks of gestation and admitted to the neonatal intensive care unit were retrospectively analysed. Demographic, clinical and laboratory data were obtained from medical records. Infants who died within the first 7 days of life were defined as the mortality group and compared with survivors. PNI was calculated using lymphocyte and albumin levels measured within the first 24 h of life. Receiver operating characteristic (ROC) analysis was used to evaluate the predictive performance of PNI for early mortality, and multi-variable logistic regression analysis was performed to identify independent predictors. Results A total of 142 infants were included, of whom 17 (12%) died within the first 7 days. Gestational age, birth weight and Apgar scores were significantly lower in the mortality group, whereas maternal smoking was more frequent. PNI values were significantly lower in infants who died (p < 0.05). ROC analysis demonstrated an AUC of 0.703 for PNI in predicting early mortality with a cut-off value of 40 (sensitivity 77%, specificity 64%). Multi-variable logistic regression analysis identified low PNI (< 40) and gestational age as independent predictors of early mortality. Conclusion PNI may serve as an adjunctive biomarker to complement established clinical predictors of early neonatal mortality in preterm infants.